2007
DOI: 10.1007/s10897-007-9132-1
|View full text |Cite
|
Sign up to set email alerts
|

How Risk is Perceived, Constructed and Interpreted by Clients in Clinical Genetics, and the Effects on Decision Making: Systematic Review

Abstract: As an individual's understanding of their genetic risk may influence risk management decisions, it is important to understand the ways in which risk is constructed and interpreted. We systematically reviewed the literature, undertaking a narrative synthesis of 59 studies presenting data on the ways in which individuals perceive, construct and interpret their risk, and the subsequent effects. While most studies assessed perceived risk quantitatively, the combined evidence suggests individuals find risk difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
127
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(145 citation statements)
references
References 106 publications
(183 reference statements)
15
127
3
Order By: Relevance
“…The literature on patient and client perceptions of risk in relation to clinical genetics illustrates that risk is an evolving social process (Sivell et al 2008). The literature emphasizes that risk perception, being dependent on the components of one's experiential knowledge at a particular point in time, is both transient and contextual.…”
Section: Laypersons' Construction Of Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on patient and client perceptions of risk in relation to clinical genetics illustrates that risk is an evolving social process (Sivell et al 2008). The literature emphasizes that risk perception, being dependent on the components of one's experiential knowledge at a particular point in time, is both transient and contextual.…”
Section: Laypersons' Construction Of Riskmentioning
confidence: 99%
“…Laypersons construct their ideas about risk in reference to multidimensional factors outside the realm of numerical labels, drawing on the subjective nature of risk (Binedell et al 1998;Brunger and Bassett 1998;Cameron et al 2009;Cox 2003;Cox and McKellin 1999;d'Agincourt-Canning 2005;Etchegary 2006a;McAllister 2002McAllister , 2003Norris et al 2009;Shiloh and Saxe 1989;Smith et al 2002). An individual's awareness of being "at-risk" is shaped by a multitude of factors including past experiences, commonsense practical knowledge, personal values, personal theories of inheritance, disease patterns, growing up in an at-risk family and stories of what constitutes someone at risk (Brorsson et al 1995;Cameron et al 2009;Cox and McKellin 1999;d'Agincourt-Canning 2005;Davison et al 1991Davison et al , 1992Etchegary 2006aEtchegary , 2006bEtchegary , 2010Etchegary and Perrier 2007;Finkler 2001Finkler , 2005Hall et al 2007;Hallowell et al 2006;Hunt et al 2000Hunt et al , 2001Katapodi et al 2004;Kenen et al 2003;Marteau et al 1995;McAllister 2002McAllister , 2003Senior et al 2002;Shedlosky-Shoemaker et al 2010;Sivell et al 2008;Weiner and Durrington 2008). Research has also shown that the meanings assigned to being at ris...…”
Section: Laypersons' Construction Of Riskmentioning
confidence: 99%
“…(2007) found that different individuals attributed the descriptor "likely" to numeric probabilities of 30-90% and "possibly" to probabilities of 5-95% (Bjorvatn et al, 2007). Indeed, it seems clear that descriptors of risk in general are typically both used and interpreted when used by others as incorporating more than numeric probability alone (Weber, 1994), and that contextual factors are of critical importance in influencing how numeric probabilities are described (Michie et al, 2005;Sivell et al, 2008); (Patt and Schrag, 2003). Given the inter-individual subjectivity and importance of context in how meaning is attached to both numeric probabilities and descriptors of risk, both are ambiguous as linguistic devices (Nessa, 1995;Noveck and Reboul 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This type of research has measured the accuracy of perceived risk, compared to an 'objective' risk estimate, and has found that many women either under- or over-estimate their risk [13-19]. Much of the research on risk perception has focused on women who attend a clinical genetics service [2,15,16,20-22] and/or women who know they carry a BRCA1 or BRCA2 mutation [23]. Two meta analyses of the effect of genetic counselling on risk perception have reported conflicting findings; one reported an increase in accuracy of risk perception due to counselling [24], while the other reported no effect [25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that the reason for variable and sometimes conflicting findings in this literature is the poor conceptualisation of risk [17,20]. It has been proposed that using objective measures of risk perception is inadequate for understanding this multi-dimensional concept [26].…”
Section: Introductionmentioning
confidence: 99%